Efficacy of high-dose vitamin D supplements for elite athletes - Owens, D. J.; Tang, J. C. Y.; Bradley, W. J.; Sparks, A. S.; Fraser, W. D.; Morton, J. P.; Close, G. L. (Medicine & Science in Sports & Exercise, 2017)
Purpose: Supplementation with dietary forms of vitamin D is commonplace in clinical medicine, elite athletic cohorts, and the general population, yet the response of all major vitamin D metabolites to high doses of vitamin D is poorly characterized. We aimed to identify the responses of all major vitamin D metabolites to moderate- and high-dose supplemental vitamin D3.